Selection bias and relationships between alcohol consumption and mortality. (February 2017) - Naimi, Timothy S.; Stockwell, Timothy; Saitz, Richard; Chikritzhs, Tanya
Abstract : Commentary to:Selection biases in observational studies affect associations between 'moderate' alcohol consumption and mortality